Emotion regulation strategies and mental wellbeing among Chinese college students during COVID-19: the moderating roles of confinement and attentional bias - Xiao, Mengqi; Wang, Yiran; Zhuang, Yaling; Luo, Yier; Liu, Li; Lin, Yingxin; Gao, Dingguo; Xu, Jiahua (Frontiers in Psychology, 2025)
BackgroundDuring COVID-19, confinement measures were implemented to curb the epidemic spread. While effective in reducing infections, these measures likely deteriorated the psychological wellbeing of students due to school closures and isolation.MethodsThis study analyzed 13,109 valid questionnaires from individuals aged 18–24 years (mean 20.28 ± 1.518) to explore how emotion regulation strategies (cognitive reappraisal and expression suppression) impact mental wellbeing through attentional biases (positive and negative), with confinement as three moderators.ResultsCognitive reappraisal was positively associated with mental wellbeing, whereas expression suppression showed a negative association. Positive attentional bias was associated with higher wellbeing, whereas negative bias was linked to lower levels of it. Negative attentional bias was linked to a stronger positive association between cognitive reappraisal and mental wellbeing, as well as a more pronounced negative association? with expression suppression. Confinement was associated with a stronger positive relation between cognitive reappraisal and mental wellbeing, while corresponding to a more negative relation with expression suppression.ConclusionOur findings highlight the complex interplay between emotion regulation strategies and mental wellbeing during confinement. Cognitive reappraisal and positive attentional bias are associated with protective effects, while expression suppression and negative bias are linked to detrimental effects. Confinement measures, despite their positive impact on physical health, significantly modulate these effects. Tailored interventions considering individual differences and contexts are needed to support mental wellbeing in similar crises.